ENGLISH BORROWING USAGE ON AUTOMOTIVE RUBRICS IN INDONESIAN MOTOBLOGS (A Morphological and Semantics Analysis) - Dimas Kusnadiaji; Jauhar Helmie (Universitas Suryakancana, 2017)
ABSTRACT This research concerns on the use of English Borrowing in the automotive article in Indonesian Motoblogs. Apart from that, there is an attempt to find out the dominate English Borrowing words that used by the article author, the reasons of an article author that used English Borrowing words in writing their article. The research was conducted by using qualitative method which is the source of data are the texts in the article of motoblogs (TMCblog.com, IwanBanaran.com, and Kobayogas.com), in collecting the data the researcher obtains the data by observing the word considered as English borrowing word from certain motoblogs, doing open ended interview to the author of motoblogs through email, and analyze every couple data with brief description based on Malmkjaer theory. The research findings showed that the types of English borrowing word that usually used by the author of automotive blog is dominated by Pure Loanword, and the reason of the author of automotive blog in applying English borrowing word in writing their article is because there is no equivalent word to shown or explain the author idea in writing the article, to shortening the word or sentence without discard the meaning, the last reason because English word are briefer and to the point in revealing the exact meaning. The researcher provide several suggestions, for lecturers it suggested could apply English borrowing word wisely especially in Morphology and Semantics class, and for students suggested that they can improve their skills and abilities in using and analyzing English Borrowing word that already used in morphology and semantics class. Keywords: Borrowing, Motoblog, Internet, Mass Media Online.